2017
DOI: 10.1111/bjep.12165
|View full text |Cite
|
Sign up to set email alerts
|

Math anxiety and math performance in children: The mediating roles of working memory and math self‐concept

Abstract: Results suggest that working memory and self-concept could be worth considering when designing interventions aimed at helping students with math anxiety. Longitudinal designs could also be used to better understand the mediational mechanisms that may explain the relationship between math anxiety and math performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 60 publications
10
75
3
4
Order By: Relevance
“…This implies that difficulties in retrieving information may in part explain the poorer performance on WM tasks by math anxious individuals observed in previous studies (e.g. Miller and Bichsel, 2004;Passolunghi et al, 2016;Justicia-Galiano et al, 2017). Given that retrieval may be engaged both in WMU and in WM tasks, further empirical work is required to determine the shared and unique associations of both WM and WMU with math anxiety.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This implies that difficulties in retrieving information may in part explain the poorer performance on WM tasks by math anxious individuals observed in previous studies (e.g. Miller and Bichsel, 2004;Passolunghi et al, 2016;Justicia-Galiano et al, 2017). Given that retrieval may be engaged both in WMU and in WM tasks, further empirical work is required to determine the shared and unique associations of both WM and WMU with math anxiety.…”
Section: Discussionmentioning
confidence: 96%
“…Since then a number of studies have confirmed impaired WM performance related to math anxiety (e.g. Miller and Bichsel, 2004;Passolunghi et al, 2016;Shi and Liu, 2016;Trezise and Reeve, 2016;Justicia-Galiano et al, 2017). Indeed, some authors have argued that WM could mediate the relationship between math anxiety and math achievement (Hartwright et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This would be very important for understanding the complex interlink between these variables during the development. Second, our instruments included several self-reported measures, which can be somewhat affected by common-method bias (Williams & Brown, 1994), and were not administered in a counterbalanced order, similarly as already done in previous studies (e.g., Justicia-Galiano, et al, 2017;Hill et al, 2016). Further research should replicate our outcomes also controlling for these small methodological issues.…”
Section: Anxiety Profiles and Protective Factorsmentioning
confidence: 99%
“…This finding supports the role of self-efficacy, which is defined as one’s self-belief about the ability to produce successful outcomes (Bandura, 1997), in reducing math anxiety (Lee, 2009). Likewise, self-concept, which refers to how the individual perceives his or her own ability in a specific discipline (Bandura, 1986; Marsh, 2006), has also been found to mediate the link between math anxiety and performance among third and fifth graders (Justicia-Galiano et al, 2017). However, other researchers have argued that low self-concept and self-esteem is the result of math anxiety (Ahmed et al, 2012).…”
Section: Within-child Factors: Biological Predispositionsmentioning
confidence: 99%